ZnO varistors from intensively milled powders - Zunic, M.; Brankovic, Z.; Bernik, S.; Goes, M. S.; Brankovic, G. (Elsevier B.V., 2007)
Two ways of application of intensive milling in ZnO varistors processing were compared. First was intensive milling of mixture of previously prepared constituent phases. In this case, intensive milling was applied only to obtain highly activated nanocrystalline varistor powder mixtures. Second application is intensive milling of simple mixture of oxides that could result not only in activation and formation of nanocrystal line powders, but also in mechanochernical reaction and synthesis of constituent phases. Powders and ceramics samples were characterized by XRD and SEM analysis. as well as by de electrical measurements (nonlinearity coefficients, leakage current and breakdown field). Differences in microstructural and electrical properties of obtained varistors were discussed and optimal milling and processing conditions were recommended. The best electrical characteristics were found in sample ZI -DMCP-m, which exhibited leakage current of 2.5 mu A/cm(2), nonlinear coefficient reaching 58 and breakdown field of 8950 V/cm. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: ZnO; varistors; milling; grain boundaries; electrical properties